Health care strategies developed by the elderly in their experience with HIV/AIDS (Research, Society and Development, 2021)
In recent years, there has been a significant increase in the number of elderly people living with HIV/AIDS. In this sense, the development of multidisciplinary strategies has contributed to guaranteeing the survival and living conditions of these people. This study aims to understand the health care strategies developed by the elderly in their experience with HIV/AIDS. This is an exploratory study, with a descriptive character and quanti-qualitative nature, developed in a specialized Care and Support Center of reference in care for people living with STIs and HIV/AIDS in a municipality in Bahia. The sample consisted of 26 people aged over 60 years diagnosed with HIV/AIDS and undergoing treatment at the referral center. As an instrument for data collection, the Mini-Mental State Examination/MMSE, a questionnaire with sociodemographic data and a semi-structured interview script were used. Qualitative data Will be analyzed and interpreted through the content proposed by Bardin. The results showed that the coping strategies developed by the HIV-positive elderly were adherence to ART, religiosity, sexual prevention, physical exercise and nutrition, in addition to obtaining institutional support from health Professionals and the family network. It is concluded that the strategies used by the elderly to cope with the disease constitute an important strengthening tool to increase longevity and encourage how to face the serological condition positively.